PRINCIPAL'S PARTICIPATIVE LEADERSHIP STYLE TO IMPROVE TEACHER PERFORMANCE IN MI AZZAINIYYAH - Rizki Kurniawan; Mulyawan Safwandy Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The purpose of this study is to find out how participative leadership improves the performance of teachers in MI Azzainiyyah and how school leaders can make decisions when teachers need to achieve quality education in schools. This study uses a qualitative approach, naturalistic techniques and triangulation. Data recovery through observation, interview and documentation, and fieldwork. In this study, researchers discussed the work of teachers. Effectiveness is therefore determined based on the evaluation and reflection of the inspector's work according to the school's goals. The results of this study show that participatory management can improve the performance of teachers, including the creation of good lesson plans with pre-primary activities, main activities and closing activities